2021
DOI: 10.3389/fpsyt.2021.651327
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors Associated With Methods of Suicide: The Korean National Investigations of Suicide Victims (The KNIGHTS Study)

Abstract: Background: Because the suicide mortality depends on the lethality of suicide methods, the identification and prediction of suicide methods are important for suicide prevention.Methods: Examination data of suicide decedents were collected based on police reports. Suicide decedents were divided into groups according to the suicide methods (hanging, gas poisoning, pesticide poisoning, jumping, drug poisoning, and drowning) they used. Predictive factors for each suicide method in comparison to other suicide metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…Suicide by hanging is the most prevalent technique, followed by suicide by gun, fire, or poison according to Younis et al [5]. The current result is different from that of Kim et al (2021), who stated that hanging was the most common method of suicide [38]. The C-SSRS has been found to be a useful tool for measuring suicide risk, capturing more of the suicide risk construct and functioning differentially between and within individuals [39].…”
Section: Resultsmentioning
confidence: 87%
“…Suicide by hanging is the most prevalent technique, followed by suicide by gun, fire, or poison according to Younis et al [5]. The current result is different from that of Kim et al (2021), who stated that hanging was the most common method of suicide [38]. The C-SSRS has been found to be a useful tool for measuring suicide risk, capturing more of the suicide risk construct and functioning differentially between and within individuals [39].…”
Section: Resultsmentioning
confidence: 87%
“…For example, one study found that 84% of people who attempted suicide had symptoms of mental disorders, and 68.3% had symptoms of depression. 12 The results of another study showed that the prevalence of depressive and anxiety disorders was high in people who attempted suicide. 27 The results of a longitudinal study showed that depression was a significant risk factor for suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality rates due to suicide are significant in different parts of the world and suicide is one of the leading causes of death worldwide, especially in youths. 12 Suicide is attempted in a variety of ways, and varies according to demographic variables such as gender and age. 13 , 14 On the other hand, suicide attempt is a global phenomenon that is seen in all parts of the world, and in Middle Eastern countries including Iran, it is a threat to public health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Arbeitsgruppe um Baldessarini [ 14 ] berechnete einen Letalitätsindex für Suizidversuche und wies darauf hin, dass Menschen mit schweren affektiven Erkrankungen in ihren Suizidversuchen ein letaleres (eher zum Tode führendes) Vorgehen wählen als Menschen ohne psychische Erkrankungen. Es gibt in der Durchführung von Suizidversuchen Unterschiede zwischen psychisch erkrankten Menschen und solchen ohne psychische Erkrankung, wie es offenbar auch bei bestimmten psychischen Erkrankungen manche Suizidmethoden häufiger gibt [ 15 ]. Außerdem bestehen im Verlauf einer psychischen Erkrankung unterschiedliche Risikokonstellationen.…”
Section: Psychische Erkrankungen Sind Die Häufigste Ursache Von Suizidenunclassified